Building a Legislative Framework for Securing Georgia’s Strategic Assets - Chochia Archil; Gvineria Shota; Mölder Holger (TalTech Journal of European Studies)
The article discusses the importance of modernizing and securing critical infrastructure in Georgia, particularly within the context of its geopolitical position and evolving economic landscape, by building an appropriate legal framework. The article outlines the signifi cant impact of cyberspace on traditional sectors such as energy, transportation, and telecommunications, necessitating a re-evaluation of critical infrastructure in the digital age. Highlighting Georgia’s aspirations to align with European and Euro-Atlantic structures for enhanced national security and democratization, the study emphasizes the need for regulatory and legislative frameworks that would be compatible with EU standards. Drawing on a comparative analysis between Estonia and Georgia, the research identifies gaps and areas for improvement in Georgia’s critical infrastructure protection (CIP) system. Through the examination of Estonia’s successful transformation from a Soviet-era environment to a robust EU-compatible CIP system, the study offers recommendations tailored to Georgia’s context.